Faktor-Faktor Yang Mempengaruhi Pendapatan Petani Gula Merah Kelapa Sawit Di Kecamatan Air Batu Kabupaten Asahan Sumatera Utara - Manurung, Azwar Anas; K, Retna Astuti; Kardhinata, Harso Kardhinata (Universitas Medan Area, 2023)
The scarcity of palm plants has resulted in brown sugar producers choosing raw materials other than palm sap, namely palm sap. Palm sap is a concern of brown sugar producers as an alternative raw material for brown sugar production so that the business of making brown sugar continues. The purpose of this study was to analyze the structure of production costs and income of brown sugar farmers from palm sap, analyze the feasibility of making brown sugar from palm sap and analyze the factors that affect the income of brown sugar farmers from palm sap in Air Batu District, Asahan Regency. . This study uses a survey method. The method of determining the sample used is using purposive sampling method using certain criteria. The research sample was 15 farmers who were included in the criteria in Air Batu District, Asahan Regency. The distribution of the sample of farmers, namely; 5 people in Pinanggripan Village, 3 people in Lake Sijabut Village, 4 people in Sijabut Teratai Village and 3 people in Hessa Bay Water Village. The research data analysis method is hypothesis testing using the methods of cost analysis, income analysis, business feasibility analysis and multiple linear regression analysis. The results of the analysis of the costs and income of the business of making brown sugar from palm sap are profitable. The results of the production BEP analysis show that the production of brown sugar is an average of 5,501.67 Kg per month, where the production is greater than the calculated BEP of 5,281.67 Kg, so the brown sugar business is declared feasible to be cultivated. The results of the BEP price analysis show that the production price is an average of Rp. 12,000/Kg where the price of brown sugar is greater than the BEP calculation of Rp. 11,281,62/Kg, so the brown sugar business is declared feasible. The results of multiple linear regression analysis showed that the results of the classical assumption test for all research variable data did not experience problems. Sugar production, capital, number of plants and sap production simultaneously have a very significant effect on the income of brown sugar farmers from oil palm sap in Air Batu District. Sugar production and capital partially have a very significant effect, while the number of plants and production of sap partially have a very significant effect on the income of brown sugar farmers from oil palm sap in Air Batu District.